2011
DOI: 10.1089/ars.2010.3491
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Induces Autophagosome Maturation Through Redistribution of the Cation-Independent Mannose-6-Phosphate Receptor

Abstract: Retinoic acids (RAs) have diverse biologic effects and regulate several cellular functions. Here, we investigated the role of RA on autophagy by studying its effects on autophagosome (AUT) maturation, as well as on upstream regulators of autophagosome biogenesis. Our studies, based on the use of pH-sensitive fluorescent reporter markers, suggested that RA promotes AUT acidification and maturation. By using competitive inhibitors and specific agonists, we demonstrated that this effect is not mediated by the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
4
24
1
Order By: Relevance
“…In a recent paper it was reported that RA enhances the acidification of autophagosomes in HeLa cells by promoting fusion with endosomes or lysosomes, and that RA in this manner contributes to increase autophagosomal maturation. 38 Our results demonstrating that RA promotes the colocalization between the autophagosomal marker LC3B and the Lyso-ID staining of lysosomes in TLR9-and CD180-stimulated cells, suggest that RA enhances autophagosomal degradation. Whether or not RA-mediated acidification and maturation of autophagosomes is involved in the RA-induced autophagosomal degradation and IgG production is, however, not yet established.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In a recent paper it was reported that RA enhances the acidification of autophagosomes in HeLa cells by promoting fusion with endosomes or lysosomes, and that RA in this manner contributes to increase autophagosomal maturation. 38 Our results demonstrating that RA promotes the colocalization between the autophagosomal marker LC3B and the Lyso-ID staining of lysosomes in TLR9-and CD180-stimulated cells, suggest that RA enhances autophagosomal degradation. Whether or not RA-mediated acidification and maturation of autophagosomes is involved in the RA-induced autophagosomal degradation and IgG production is, however, not yet established.…”
Section: Discussionsupporting
confidence: 49%
“…RA has previously been linked to autophagy in other cell types and under other conditions. 38,49,50 In acute promyelocytic leukemia (APL) cells we found RA to induce autophagy-mediated degradation of the PML-RARA (promyelocytic leukemia/ retinoic acid receptor a) fusion oncoprotein. 49 The effect of RA in the APL cells was mediated via inhibition of the MTOR (mechanistic target of rapamycin [serine/threonine kinase]) pathway, and interestingly, siRNA against ULK1 diminished the autophagy-induced degradation of the PML-RARA fusion oncoprotein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot and immunohistochemistry analysis described the increase degradation of 14-3-3ζ protein of lysosome in the absence of TTR, increasing autophagy and memory deficits process [38] [79] [80] [81] [82]. In conclusion, the absence of TTR decreases 14-3-3ζ protein levels in the hippocampus which in turn attributable to increased degradation in the lysosomal compartments, probably by the reduced levels of 14-3-3ζ protein [83] [84].…”
Section: Role In the Maintenance Of Learning And Memory Capacities Ofmentioning
confidence: 99%
“…ATRA may also have a biologic role in autophagosome maturation through the redistribution of a cation-dependent mannose-6-phosphate receptor (CIMPR) to the developing autophagosome, leading to vesicle acidification. This effect is thought to be independent of nuclear hormone receptors and instead to be mediated by direct binding of ATRA to CIMPR 131 . A recent study indicates that ATO induces autophagy via the induction of MEK/ERK signaling independently of the mTOR autophagy-signaling axis 103 .…”
Section: Autophagy In Apl Cell Differentiationmentioning
confidence: 99%